Mass. Gen. Stat. 255, ch. 49, § 27 (1873) - (:unkn) unknown (My University, 1859)
Appointed six individuals in each county for proving of musket barrels and pistols. Proven arms are stamped by the appointed officials.
Keywords: MANUFACTURE ONLY